Light microscopy in biology : a practical approach - Lacey, Alan J. (Practical approach series., 1999)
"Since the first edition of Light Microscopy in Biology: A Practical Approach was published, techniques in modern light microscopy have improved considerably. This fully updated edition includes revised topics from the first edition as well as coverage of techniques and technologies that have been developed since it was published." "This new edition will be of great interest to postgraduate and postdoctoral researchers in biomedicine and cell biologyboth those experienced with light microscopic techniques and newcomers to the field."--Jacket